Self-switchable polymer reactor with PNIPAM-PAm smart switch capable of tandem/simple catalysis - Wei, Wenjing; Thakur, Vijay Kumar; Li, Songjun; Chianella, Iva (Elsevier, 2021)
In this paper, we report a novel three-layer polymer reactor capable of simple/tandem self-controlled catalysis. The top and bottom layers were composed of two different molecularly imprinted polymers respectively containing two catalytic sites (an acidic site catalyzing hydrolysis and metal nanoparticles catalyzing reduction), performing two selective tandem reactions without interference between each other. The middle layer was composed of a copolymer of poly-N-isopropylacrylamide (PNIPAM) and polyacrylamide (PAm) in different ratio, acting as a temperature-responsive switch for the tandem catalysis process. In an aqueous environment, when the temperature is lower than the Lower Critical Solution Temperature (LCST) of the copolymer, the reactor exhibited an open middle access (hydrophilic condition) of intermediate, allowing the tandem processes from hydrolysis to reduction. When the temperature is higher than the LCST, the channels of the middle layer were closed (hydrophobic condition), which obstructed the access of reactants. As a result, the reactor could only conduct simple hydrolysis processes. Therefore, with the three-layer structure, the polymer reactor has led to a self-controlled catalysis. This new multi-layer polymeric reaction concept can expand the practical use of functional catalysts by permitting the control of processes in large temperature ranges.
Keywords: Temperature-responsive polymer; Tandem catalysis; LCST; Smart catalysis